Pretibial myxedema exhibiting prominent asymmetrical manifestations - Sawada, Tomoya; Otsuka, Atsushi; Tsujioka, Kaoru (Trends in Immunotherapy, 2022)
Pretibial myxedema (PTM) is an uncommon cutaneous manifestation of Graves’ disease. A 62-year-old obese Japanese man treated for Graves’ disease presented with nodular lesions symmetrically on both pretibial areas. Systemic corticosteroid therapy targeted against simultaneously developing severe Graves’ ophthalmopathy almost completely cleared his skin symptoms. About ten years later, edema of both lower legs recurred, and the right lower leg showed an elephantiasis-like condition with nodules. However, the left leg had less edema and only a few nodular lesions. The skin lesions gradually improved with oral prednisolone. We speculate that our patient’s habit of lying on the right side of the body induced prominent asymmetry of skin lesions by pooling some immune mediators.